Gatifloxacin‐1, 2, 3‐triazole‐isatin hybrids and their antimycobacterial activities. Issue 10 (22nd August 2019) - Ding, Zhen; Hou, Panfei; Liu, Bi
Abstract: A series of gatifloxacin‐1, 2, 3‐triazole‐isatin hybrids8a–l were designed, synthesized, and screened for their in vitro antimycobacterial activity as well as cytotoxicity toward Chinese Hamster Ovary (CHO) cells. The synthesized hybrids showed considerable activity against MTB H37 Rv and two MDR‐MTB strains with minimal inhibitory concentration (MIC) of 0.25–8 μg/ml, and the hybrid8a (MICMTB H37Rv : 0.25 μg/ml and MICMDR‐MTB : 0.5 and 1 μg/ml) was found to be most active against the tested strains, which was not inferior to the parent gatifloxacin (MIC: 0.5, 0.25, and 0.5 μg/ml) against all three tested strains, and was ≥128‐fold more active than isoniazid (MIC: ≥64 μg/ml) and rifampicin (MIC: >128 μg/ml) against the two MDR‐MTB strains. Moreover, hybrid8a (CC50 : 8.0 μg/ml) also displayed acceptable cytotoxicity toward CHO cells, and the selectivity index was 32. The structure–activity relationship and structure–cytotoxicity relationship were also enriched. Abstract : Twelve gatifloxacin‐1, 2, 3‐triazole‐isatin hybrids8a–l were designed, synthesized, and examined for their in vitro antimycobacterial activity against both drug‐sensitive and multidrug‐resistant MTB strains. The hybrid8a was not inferior to the parent gatifloxacin against three tested strains and demonstrated acceptable cytotoxicity toward Chinese Hamster Ovary cells, making this kind of hybrids promising lead molecules for further optimization.